Global tariff war : economic, political and social implications - Das, Ramesh Chandra, 1973- (Emerald Publishing Limited, 2021)
'Global Tariff War: Economic, Political and Social Implications' traces the range of impacts that global tariff wars in international trade can have on the growth and expansion of national economies. The Global economic and political status quo has faced turmoil after the US President's 2018 announcement on the imposition of import tariff steel and aluminium products. Taking as its core focus the trade war between the USA and China, this book focuses impact on the rest of the world's economies, and explores key areas including neo-protectionism, globalization and restricted trade, inflation volatility, FDI and tariff rates, and the environmental footprint of global trade tariffs. Having previously played the role of campaigner in favour of free trade since the World War II, today's United States has projected itself towards greater protectionism and patriotism. Conclusions arise that tariff wars, as well as trade wars, are damaging for national and transnational economies, as well as other sectors, such as society and environment. Evidence presented in the work illustrates that developed countries are impacted more adversely in comparison to developing zones due to this type of tariff war. Offering a range of illuminating perspectives from under explored developing economies being directly affected by these policies, this collection presents a unique critical insight into this complex and evolving area of geo-political and economic practice.
Includes index.
Keywords: Tariff.; International economic relations.; Tariff -- United States.; Tariff -- China.; United States -- Foreign economic relations -- China.; China -- Foreign economic relations -- United States.; Business & Economics -- International -- Economics.; International trade.; elektronické knihy; electronic books